2015
DOI: 10.1371/journal.pone.0115836
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Seroprevalence of Epstein-Barr Virus in Taiwan

Abstract: BackgroundEpstein-Barr virus (EBV) causes a variety of clinical manifestations from asymptomatic infection to acute infectious mononucleosis in human. Moreover, the EBV infection is associated with malignancies. The large-scale EBV seroepidemiology across all age groups has been lacking in Taiwan.MethodsA total of 1411 serum samples were tested to examine the seroprevalence of EBV in 2007. The samples were collected during an island-wide seroepidemiological survey of vaccine preventable diseases in Taiwan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 43 publications
11
58
3
Order By: Relevance
“…EBV spread requires intimate contact, and epidemiologic studies have identified the socioeconomic status and hygienic behavior as main factors for EBV acquisition . A marginally but significantly higher risk of EBV detection was reported in tonsil brushings among current tobacco smokers, in agreement with some, but not all, large seroepidemiologic studies. The risk of EBV infection study was not associated with any other studied variables including neither sex, as in most previous studies, nor indication of tonsillectomy, even though it has been suggested that EBV may play a role in the pathogenesis of recurrent tonsillitis …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…EBV spread requires intimate contact, and epidemiologic studies have identified the socioeconomic status and hygienic behavior as main factors for EBV acquisition . A marginally but significantly higher risk of EBV detection was reported in tonsil brushings among current tobacco smokers, in agreement with some, but not all, large seroepidemiologic studies. The risk of EBV infection study was not associated with any other studied variables including neither sex, as in most previous studies, nor indication of tonsillectomy, even though it has been suggested that EBV may play a role in the pathogenesis of recurrent tonsillitis …”
Section: Discussionsupporting
confidence: 88%
“…HHVs are generally acquired in the childhood or in adolescence, and most primary infections remain asymptomatic or induce mild and unspecific symptoms. The one defining characteristic of HHVs is their inherent capacity to evade the host's immune system, thereby establishing lifelong latent infections that can reactivate particularly in immunocompromised or immunosuppressed hosts to cause recurrent infections .…”
Section: Introductionmentioning
confidence: 99%
“…In the Asian population, EBV seroprevalence is particularly evident in children <3 years of age (50%) and >8 years of age (90%), potentiating the interest in the development of an EBV vaccine [9], as reported in a Thai study on primary EBV infection [14]. Indeed, a previous Thai study documented the early age of development of PI and established an ideal target age for vaccination before 7 years of age in this population [15]. Instead, in the American population, different articles reported socioeconomic differences in EBV seroprevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, EBV infection is necessary for NPC progression. By adulthood, approximately 90% of individuals are EBV infected 12,13. Although EBV is a ubiquitous pathogen, EBV-associated NPC develops in only a small fraction of infected individuals.…”
Section: Introductionmentioning
confidence: 99%